Analysis the Effect of Effective Tax Rate, Tunneling Incentive, Bonus Mechanism and Debt Covenant towards Company Transfer Pricing Decision - Lindawati, ASL; Ivani, (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the influence of effective tax rate, tunneling incentive, bonus mechanism and debt covenant towards transfer pricing decision in agriculture and mining companies. The population used based on main sectors companies that listed in Indonesia Stock Exchange period of 2016-2018. The sample was taken by purposive sampling and resulted in the final sample of 42 companies. Data collection were taken from the company's annual report and analyzed by logistic regression as an analysis tool. The results and discussion of the logistic regression show that tunneling incentive has a positive effect on transfer pricing decision. While others independent variables have no effect on transfer pricing decision.